2010
DOI: 10.1086/652749
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Inflammation, Coagulation, and Renal Function Are Elevated in Adults with HIV Infection

Abstract: Background HIV replication and immune activation may increase inflammation and coagulation biomarkers. Limited data exist comparing such biomarkers for those with and without HIV infection. Methods For those aged 45–76, high sensitivity C-reactive protein (hsCRP), interleukin-6 (IL-6), D-dimer, and cystatin C were compared for 494 HIV-infected individuals in the Strategies for Management of Anti-Retroviral Therapy (SMART) study with 5,386 participants in the Multi-Ethnic Study of Atherosclerosis (MESA). For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

36
600
6
17

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 757 publications
(659 citation statements)
references
References 30 publications
36
600
6
17
Order By: Relevance
“…39 Subjects infected with HIV-1 have increased levels of hs-CRP, TNF alpha (TNF-a), IL-6, d-dimer, and other biomarkers compared with HIV-negative subjects. 2,[40][41][42] These elevations in biomarkers persist even after virologic suppression, likely due to HIV-induced activation of inflammation and coagulation pathways. 2 Levels of TNF-a, IL-6, hs-CRP, and other proinflammatory cytokines are associated with HIV-1 viral load and may predict disease progression, as well as correlate with a higher risk of CVD and all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Subjects infected with HIV-1 have increased levels of hs-CRP, TNF alpha (TNF-a), IL-6, d-dimer, and other biomarkers compared with HIV-negative subjects. 2,[40][41][42] These elevations in biomarkers persist even after virologic suppression, likely due to HIV-induced activation of inflammation and coagulation pathways. 2 Levels of TNF-a, IL-6, hs-CRP, and other proinflammatory cytokines are associated with HIV-1 viral load and may predict disease progression, as well as correlate with a higher risk of CVD and all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%
“…2,[40][41][42] These elevations in biomarkers persist even after virologic suppression, likely due to HIV-induced activation of inflammation and coagulation pathways. 2 Levels of TNF-a, IL-6, hs-CRP, and other proinflammatory cytokines are associated with HIV-1 viral load and may predict disease progression, as well as correlate with a higher risk of CVD and all-cause mortality. [42][43][44][45] Our findings corroborate another recent analysis, which reported that only d-dimer, and not IL-6 or hs-CRP, is reduced over the short term in those initiating ARV therapy.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] Lifestyle factors such as smoking and substance misuse are much higher in HIV-positive patients, 13,14 and HIV-positive patients are also more likely to experience dyslipidaemia and often have other chronic conditions that increase the risk of severe non-AIDS morbidity. 15 Furthermore, antiretroviral treatment (ART) increases the rates of dyslipidaemia, insulin resistance and diabetes. 16,17 Finally, HIV infection itself appears to be associated with age-related complications.…”
Section: Introductionmentioning
confidence: 99%
“…Pengaruh terapi antiretroviral dalam mengatasi hal tersebut belum diketahui dan sulit untuk ditentukan karena dinilai memiliki efek toksik terhadap organ-organ tersebut. 22 Sebuah studi melaporkan bahwa angka kejadian osteopenia dan osteoporosis tiga kali lebih tinggi pada populasi HIV. Fraktur juga lebih sering dijumpai pada pasien HIV.…”
Section: Penyakit Hati Ginjal Dan Tulangunclassified